Occurrence, spatial-temporal distribution and ecological risks of pharmaceuticals and personal care products response to water diversion across the rivers in Nanjing, China. (December 2019) - Yang, Haohan; Lu, Guanghua; Yan, Zhenhua; Liu, Jianchao; Dong, Huike; Jiang, Runren; Zhou, Ranran; Zhang, Peng; Sun, Yu; Nkoom, Matthew
Abstract: Water diversion projects have been continuously used to alleviate water quality issues that arise during urbanization. However, studies about whether it has possible effects on the status of pharmaceutical and personal care products (PPCPs) are limited. In this study, the occurrence trends and spatial-temporal distribution characteristics of 50 PPCPs were investigated in surface water, suspended particulate matter (SPM) and sediments in Nanjing urban rivers under the background of the water diversion project from the Yangtze River to the Qinhuai River. In the four field campaigns that were embarked on April to July 2018, a total of 40, 38 and 24 PPCPs were detected in surface water, SPM and sediments, respectively, with overall concentrations of 138–1990 ng/L, 3214–33, 701 ng/g and 12.1–109 ng/g dry weight (dw) among nine sampling sites. The excessive concentration of caffeine (20.6–905 ng/L) may be evidence of the direct discharge of untreated sewage and an obvious indicator of the overall concentrations of PPCPs. The PPCPs contamination levels in surface water were increased along with the direction of the water diversion in urban runoff, and decreased by 8–31% due to the increase in volume attributable to the water diversion. The distribution coefficients ( K d ) of pollutants in the SPM-water phases (3.0–5.6 L/kg) were two orders of magnitude higher than those in the sediment-water phases (0.3–3.3 L/kg). And the positive correlations between their log K ow and SPM-water log K d values indicated SPM was the important carrier determining the fate of organic UV filters. Furthermore, the results of ecological risk assessment demonstrated that although the increase in the volume of water caused by the water diversion reduced the overall ecological risks of PPCPs in urban rivers, the current contamination level still represents high risks to algae and fish. Graphical abstract: Image 1 Highlights: The concentration of PPCPs with respect to the water diversion project in the Nanjing Qinhuai River was investigated. Water diversion can improve the PPCP contamination levels through scouring and dilution. The high concentration of caffeine was a significant indicator of the overall concentration. Suspended particulate matter was the important carrier determining the fate of organic UV filters. The overall ecological risks of the detected PPCPs to algae and fish were still at high levels. Abstract : Main finding of the work: The water diversion project from the Yangtze River to the Qinhuai River is an operative measure to relieve the contamination level of PPCPs in urban runoff.